Ideological Think Tanks in the States: An Inventory of Their Prevalence, Networks, and Higher Education Policy Activity. (March 2014) - Ness, Erik C.; Gándara, Denisa
This study takes an inventory of a particular type of intermediary organization ascendant within the state-level higher education policy: ideological think tanks. Our inventory identifies 99 think tanks: 59 affiliated with the conservative State Policy Network and 40 with the Progressive States Network. The analysis shows that state-level conservative think tanks (CTTs) are more tightly connected to national networks than are progressive think tanks (PTTs). By narrow margins, CTTs are also better funded and have more robust higher education policy activity than PTTs. The two most common policy issues—state funding and costs and affordability—represent higher education issues of equal salience to conservative and progressive organizations but from contrasting ideological perspectives. This inventory of the landscape of ideological think tanks' activity and their supply of information has implications for future research that might examine policymakers' demand for and utilization of ideological think tank information and services.